PWE-117 Have Perianal Surgery Rates Decreased With The Rise In Thiopurine Use In Crohn's Disease?. (9th June 2014) - Chhaya, V; Saxena, S; Cecil, E; Subramanian, V; Curcin, V; Majeed, A; Pollok, R
Abstract : Introduction: Although thiopurines (TPs) have proven efficacy in the maintenance of remission in Crohn's disease (CD) and may reduce the need for intestinal surgery, their impact on perianal disease is not firmly established since previous trials have not evaluated the efficacy of TPs on perianal disease as a primary endpoint. Our aim was to examine the temporal trends in perianal surgery and TP use using the Clinical Practice Research Datalink (CPRD). Methods: Using electronic primary care records, we performed a UK population based study. Incident cases of CD were identified between 1995 and 2009 from the nationally representative CPRD which contains clinical records and prescribing data for 13 million people in the UK and is a validated research database. Patients were included if they had been registered with a practice for greater than 12 months. The primary endpoint was first perianal surgery defined by READ/OXMIS coding. The cohort was divided into two defined historical era; era 1 (1995–2002) and era 2 (2003–2009). We performed Kaplan-Meier survival analysis to establish the 5 year rates of first perianal surgery and trends in TP prescribing by era of diagnosis. Log-rank test for trend was used to compare survival outcomes between groups. Results: 5235 patients met the diagnostic criteria for an incident case of CD. 2083 were diagnosed in era 1 (1995–2002) and 3152 in era 2 (2003–2009). The mean duration of follow up was 4.8 years/person. 56.3% of patients were female and median age at diagnosis was 38.5 years (IQR: 24.8–58.1 years). 124 patients underwent perianal surgery. The overall 5 year rate of perianal surgery was 2.2% (95% CI: 1.8–2.7%). Stratified by era of diagnosis the rate was lower in the more recent era: 2.7% (95% CI: 2.1–3.6%) and 1.7% (95% CI: 1.2–2.3%) in era 1 and era 2 respectively (log-rank test for trend p = 0.03). Conversely, during the same period, the 5 year cumulative probability of receiving a TP increased between era 1 and era 2 from 29.1% to 42.2% (log-rank test for trend p < 0.001). Conclusion: Over the 15 year study period, the risk of perianal surgery fell by one third which coincided with a one third increase in TP use during the same period. Other changes in IBD management are also likely to have contributed to this fall in surgery. Further studies to determine independent risk factors associated with perianal surgery are in progress. Disclosure of Interest: None Declared.